PENGARUH KONSERVATISME AKUNTANSI DAN GOOD CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT - LIAN SARI, MEIRY (Jurnal Akuntansi AKUNESA, 2018)
This study aims to explain and analyze the influence of accounting conservatism and Good Corporate Governance on earnings management in manufacturing companies listed on the Stock Exchange in 2012-2015. Accounting conservatism is measured by subtracting corporate income before tax deducted by the companys operating cash flow, measuring GCG by using a percentage of managerial ownership, institutional ownership, independent commissioners and audit committees. While earnings management is measured using discretionary accruals. The sample used in this study was 148 of the 37 companies that published full reports from 2012-2015. This study found that accounting conservatism and good corporate governance did not affect earnings management. In conclusion, from this study accounting conservatism and GCG have not been able to minimize the practice of earnings management.Keywords: Accounting conservatism, Earnings management, GCG